2016
DOI: 10.1088/0957-4484/27/41/415602
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of SPIONs: role of phosphonate ligand multivalency in tailoring their efficacy

Abstract: We report the design of scaffolds containing mono-, bis-, and tris-phosphonate coordinating groups, and a polyethylene glycol chain, for stabilizing superparamagnetic iron oxide nanoparticles (SPIONs), using simple and versatile chemistry. We demonstrate that the number of anchoring phosphonate sites on the ligand influence the colloidal stability, magnetic and biological properties of SPIONs, and the latter do not solely depend on attaching moieties that can enhance their aqueous dispersion. These parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…In these different cases of chemisorption, multivalency is an important way to increase the binding strength e.g. with bis-or triphosphonates [124,125] or with polyacids such as phosphonate end-terminated sidechains [126] or polyacrylates. The grafting-to method provides a great versatility of the surface modification as well with synthetic and natural polymers.…”
Section: Formulation Of Drugs and Magnetic Nps In Thermally Sensitivementioning
confidence: 99%
“…In these different cases of chemisorption, multivalency is an important way to increase the binding strength e.g. with bis-or triphosphonates [124,125] or with polyacids such as phosphonate end-terminated sidechains [126] or polyacrylates. The grafting-to method provides a great versatility of the surface modification as well with synthetic and natural polymers.…”
Section: Formulation Of Drugs and Magnetic Nps In Thermally Sensitivementioning
confidence: 99%
“…These suggested that spherical structures were formed with a size distribution of 200 and ~60 nm, as measured by DLS and TEM respectively. As is common with solution based DLS measurements, hydrodynamic sizes of these assemblies were found to be higher as compared to TEM [37]. We were unable to obtain a critical micelle concentration of the assembled structures using pyrene encapsulation.…”
Section: Synthesismentioning
confidence: 75%
“…The different types of IO used for the NPs synthesis include Fe3O4 (magnetite), α-Fe2O3 (hematite or antiferromagnetic), c-Fe2O3 (maghemite, ferrimagnetic), FeO (wustite, anti-ferromagnetic), γ-Fe2O3 and β-Fe2O3. However, Fe3O4 and γ-Fe2O3 NPs are the favorable and most commonly used chemical forms that are specially designed for various biomedical applications such as imaging contrast agents for MRI, thermal therapeutic tools [25,26] and as cargo vehicles due to their features of improved biocompatibility and easy formulation [27][28][29][30]. These are structurally constituted, having nanocrystalline magnetite Fe3O4 or γ-Fe2O3 with a polymeric coating.…”
Section: Iron Oxide (Io)-npsmentioning
confidence: 99%
“…can be considered to modify the surface of IONPs, i.e., organic and inorganic coatings [27]. The organic biocompatible based coating approaches are by either using a ligand exchange mechanism or physical assemblage/encapsulation [28]. Inorganic biocompatible coating involves the use of silica, Tantalum (V) Oxide.…”
Section: Fig 2: Types Of Nps and Their Multifunctional Strategiesmentioning
confidence: 99%